Feud: Hatfields, McCoys and Social Change in Appalachia, 1860-1900 - Fellman, Michael (Labour / Le Travail, 1989)
The article reviews the book, "Feud: Hatfields, McCoys and Social Change in Appalachia, 1860-1900," by Altina L. Waller.
Keywords: FEUD: Hatfields, McCoys & Social Change in Appalachia 1860-1900 (Book); Nonfiction; REVIEWS; Social change; WALLER, Altina L.; books